Understanding and improving the quality of primary care for people in prison: a mixed-methods study - Sue Bellass; Krysia Canvin; Tracey Farragher; Kate McLintock; Nat Wright; Pip Hearty; Nicola Seanor; Marie Cunningham; Robbie Foy; Laura Sheard (NIHR Journals Library, 2024)
Background People in prison are generally in poorer health than their peers in the community, often living with chronic illness and multimorbidity. Healthcare research in prisons has largely focused on specific problems, such as substance use; less attention has been paid to conditions routinely managed in primary care, such as diabetes or hypertension. It is important to understand how primary care in prisons is currently delivered in the United Kingdom and how it can be improved, in order to reduce health inequalities. Objective To understand the quality of primary care in prison, including gaps and variations in care, in order to recommend how quality of prison health care can be improved. Design A mixed-methods study with six interlinked work packages. Setting Predominantly the North of England. Methods Between August 2019 and June 2022, we undertook the following work packages: (1) International scoping review of prison healthcare quality indicators. (2) Stakeholder consensus process to identify United Kingdom focused prison healthcare quality indicators. (3) Qualitative interview study with 21 people who had been in prison and 22 prison healthcare staff. (4) Quantitative analysis of anonymised, routinely collected data derived from prison healthcare records (~ 25,000 records across 13 prisons). (5) Stakeholder deliberation process to identify interventions to improve prison health care. (6a) Secondary analysis of the qualitative data set, focusing on mental health and (6b) analysis of the quantitative data set, focusing on health care of three mental health subgroups Findings Our scoping review found predominantly only papers from the United States of America and of variable rigour with the main finding being that performance measurement is very challenging in the prison healthcare setting. In collaboration with stakeholders, we prioritised, refined and applied a suite of 30 quality indicators across several healthcare domains. We found considerable scope for improvement in several indicators and wide variations in indicator achievement that could not be attributed to differences in prison population characteristics. Examples of indicators with scope for improvement included: diabetes care, medicines reconciliation and epilepsy review and control. Longer length of stay in prison was generally associated with higher achievement than shorter stays. Indicator achievement was generally low compared to that of community general practice. We found some encouraging trends and relatively good performance for a minority of indicators. Our qualitative interviews found that quality of health care is related to factors that exist at several levels but is heavily influenced by organisational factors, such as understaffing, leading to a reactive and sometimes crisis-led service. Our stakeholder deliberations suggested opportunities for improvement, ideally drawing on data to assess and drive improvement. Our mental health work package found that coded mental illness had mixed associations with indicator achievement, while the interviews revealed that mental distress is viewed by many as an inevitable facet of imprisonment. Limitations Our analyses of indicator achievement were limited by the quality and coverage of available data. Most study findings are localised to England so international applicability may differ. Conclusions Marked variations in the quality of primary care in prisons are likely to be attributable to the local organisation and conditions of care delivery. Routinely collected data may offer a credible driver for change. Study registration This study is registered at researchregistry.com (Ref: 5098). Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: 17/05/26) and is published in full in Health and Social Care Delivery Research; Vol. 12, No. 46. See the NIHR Funding and Awards website for further award information. Plain language summary People in prison often have health that is worse than people who live in the community. We do not know much about the quality of prison health care (how good it is). We also do not know much about what happens when people in prison go to see their doctor or nurse for common conditions, like asthma or diabetes. We need to understand how the quality of prison health care can be made better. This is the purpose of this study. Between 2019 and 2022, we worked with people who had knowledge about prison health care, and they helped us focus on what was most important about clinical aspects of the quality of prison health care. We looked at 25,000 prison medical records to see if there were patterns in the data (the medical records were anonymous, so we did not know who was who). There were big differences between prisons. People who were in prison with a long sentence had better-quality health care than those with a short sentence. We talked with 21 people who had been in prison and 22 prison healthcare staff who told us that quality could be influenced by many different things. They told us that one of the biggest issues was not enough healthcare staff in each prison. We took a closer look at mental health and found that health care was sometimes better for people with mental illness and sometimes worse. Mental distress was considered part of prison life by many people. Overall, we found that there is a large amount of difference in the quality of prison health care. This is probably related to how health care is organised in local areas and prisons. Scientific summary Background Compared to community populations, people in prison have significantly poorer health, with higher levels of long-term conditions, disability, and premature death. They need and are entitled to appropriate health care. Most research on prison health care has previously focused on specific priorities, such as mental illness, blood-borne virus infections and substance misuse. However, less attention has been paid to the quality of 'routine' primary care. This is important given shifting demographics, including an ageing population with more long-term conditions, and the opportunities to improve outcomes through primary and secondary prevention. We examined the quality of primary care in prison and identified strategies for improvement. Objectives To identify quality indicators based on current national guidance which can be assessed using routinely collected data through a stakeholder panel. To explore perceptions of quality of care, including barriers to and enablers of recommended care and quality indicators, through qualitative interviews involving people who had been in prison and prison healthcare staff. To assess the quality of primary care provided to people in prison through analysis of anonymised and routinely held prison healthcare records. To integrate the above findings and identify quality-improvement interventions which can be monitored by our set of quality indicators. To understand quality of prison health care in relation to mental health needs. Methods and findings Our mixed-methods programme had interlinked work packages (WPs) closely aligned to our objectives. It ran from August 2019 to July 2022 with research fieldwork and analyses over November 2019 to May 2022. Identification of quality indicators (WP1) Scoping review Methods We first conducted an international scoping review to describe existing literature on the development and selection of quality indicators for primary health care in the prison setting. We searched for articles published in English between 2004 and 2021. Our broad inclusion criteria included any research method, any health condition, and any country. We excluded papers relating to community criminal justice settings and on transitions from prison to community. We searched six electronic databases (MEDLINE, CINAHL, Scopus, EMBASE, PsycInfo and Criminal Justice Abstracts) supplemented by hand searching of four key journals, key author searches and forwards and backwards citation tracking. We performed a qualitative synthesis of eligible papers. Findings Of 1271 records screened, 24 were eligible for full text review and 15 were included. The literature was predominantly from the USA. Our synthesis found that rigour and stakeholder involvement in the selection of quality indicators varied, with no paper including patient representation.